The flowering of SDP chrysanthemum in response to intensity of supplemental or night-interruptional blue light is modulated by both photosynthetic carbon assimilation and photoreceptor-mediated regulation - Yang, Jingli; Song, Jinnan; Jeong, Byoung Ryong (Frontiers in Plant Science, 2022)
The photoreceptor-mediated photoperiodic sensitivity determines the obligate short-day flowering in chrysanthemum (Chrysanthemum morifolium Ramat.) when the night length is longer than a critical minimum, otherwise, flowering is effectively inhibited. The reversal of this inhibition by subsequent exposure to a short period of supplemental (S) or night-interruptional (NI) blue (B) light (S-B; NI-B) indicates the involvement of B light-received photoreceptors in the flowering response. Flowering is mainly powered by sugars produced through photosynthetic carbon assimilation. Thus, the light intensity can be involved in flowering regulation by affecting photosynthesis. Here, it is elucidated that the intensity of S-B or NI-B in photoperiodic flowering regulation of chrysanthemums by applying 4-h of S-B or NI-B with either 0, 10, 20, 30, or 40 μmol·m−2·s−1 photosynthetic photon flux density (PPFD) in a 10-h short-day (SD10) [SD10 + 4B or + NI-4B (0, 10, 20, 30, or 40)] or 13-h long-day (LD13) condition [LD13 + 4B or + NI-4B (0, 10, 20, 30, or 40)] provided by 300 ± 5 μmol·m−2·s−1 PPFD white (W) LEDs. After 60 days of photoperiodic light treatments other than the LD13 and LD13 + NI-4B (40), flowering with varying degrees was observed, although the SD10 gave the earliest flowering. And the LD13 + 4B (30) produced the greatest number of flowers. The flowering pattern in response to the intensity of S-B or NI-B was consistent as it was gradually promoted from 10 to 30 μmol m−2 s−1 PPFD and inhibited by 40B regardless of the photoperiod. In SD conditions, the same intensity of S-B and NI-B did not significantly affect flowering, while differential flowering inhibition was observed with any intensity of NI-B in LDs. Furthermore, the 30 μmol·m−2·s−1 PPFD of S-B or NI-B up-regulated the expression of floral meristem identity or florigen genes, as well as the chlorophyll content, photosynthetic efficiency, and carbohydrate accumulation. The 40B also promoted these physiological traits but led to the unbalanced expression of florigen or anti-florigen genes. Overall, the photoperiodic flowering in response to the intensity of S-B or NI-B of the SDP chrysanthemum suggests the co-regulation of photosynthetic carbon assimilation and differential photoreceptor-mediated control.